(untitled) (Harmoni, 2020)
This study is entitled ΓÇ£The Effectiveness of BP4 counselors in Suppressing Divorce Rates in Makassar CityΓÇ¥ The research questions comprise: 1) What are the factors instigating divorce inMakassar City? 2) What are the efforts performedby BP4 counselors to reduce divorce rate inMakassar city? The research was conducted atfive KUA in Makassar city. It is a qualitative typeof research aimed at presenting descriptive datathrough employment of descriptive-critical dataanalysis techniques. Key informants involve theheads of the five KUA and BP4 instructors. Theresults of the research indicate that the factorsinstigating divorce in Makassar city include lackof responsibility from the part of the husbandsin supporting livelihood, domestic violence, anddisloyalty (on account of new lifestyles adoptedthrough the influence of the social media). BP4counselors have actually carried out their dutiesand functions to the fullest, but sometimes theystill face obstacles, especially the lack of timefor the prospective marriage couples to attendSuscatin (pre marriage briefing) sessions as wellas budgetary constraints in placing counseling.Additional obstacle experienced by the counselorsin suppressing divorce rate is the negligence ofmarried couples suing divorce in visiting the localKUA office to get counseling. Broadly put, theeffectiveness of BP4 counselors in suppressingdivorce rate in Makassar City is still not optimum.